Unravelling the role of health literacy among individuals with multimorbidity: a systematic review and meta-analysis - Marjan Van Den Akker; Sailesh Mohan; Sanghamitra Pati; Andrea F de Winter; Girish Chandra Dash; Janine de Zeeuw; Pranab Mahapatra; Arohi Chauhan; Fernando Gregorio Linares-Jimenez; Archana Kumawat (BMJ Open)
Objective To examine existing literature regarding health literacy levels and their association with multimorbidity and the potential underlying mechanisms behind the said association.Design Systematic review and meta-analysis.Data sources The databases MEDLINE, EMBASE, CINAHL and Science Direct were searched for articles published between 1 January 2000 and 31 October 2023 using a systematic search strategy.Eligibility criteria Included were all primary studies conducted in people over 18 years old with data on health literacy levels and the presence of multimorbidity. No language restrictions were used.Data extraction and synthesis Two authors independently extracted data and assessed the bias using the Joanna Briggs Institute critical appraisal tools.Results We included a total of 39 studies (36 quantitative, two qualitative and one mixed-method), representing 154 337 participants. We found a 32% proportion of limited health literacy among individuals with multimorbidity. Analysis of three articles using the Health Literacy Questionnaire tool (n=31 228) (Pooled OR 2.88 (95% CI 1.92 to 4.31)) and three articles using the Health Literacy Survey Questionnaire–European Union tool (n=35 358) (OR 1.16 (95% CI 1.07 to 1.25)) indicated that people with limited health literacy were likely to have multiple conditions. One of three articles studying underlying mechanisms reported that self-efficacy mediates the association between health literacy and multimorbidity. Additionally, substantial literature identified education and income as the most consistent determinants of health literacy among individuals with multimorbidity. Of the only two articles studying the effectiveness of health literacy-related interventions, both reported an improvement in clinical outcomes after the intervention.Conclusions Our review demonstrated a consistent association between health literacy and multimorbidity, indicating that people with lower health literacy levels are more likely to have multimorbidity. More evidence is needed regarding the effect of health literacy interventions on multimorbidity.PROSPERO registration number CRD42022301369.